Comparison of quercetin and rutin inhibitory influence on Tartary buckwheat starch digestion in vitro and their differences in binding sites with the digestive enzyme. (15th January 2022) - Wang, Libo; Wang, Lijuan; Wang, Tongtong; Li, Zaigui; Gao, Yanxiang; Cui, Steve W.; Qiu, Ju
Highlights: Quercetin and rutin decrease the digestibility of starch in Tartary buckwheat. Quercetin has a lower IC50 than rutin suggesting the better enzyme inhibition. Rutin interacts with enzymes mainly by CH and OH on the glycoside structure. Steric hindrance of glycoside structure in rutin restricts its inhibitory property. Alpha-amylase exhibits a better affinity for phenolic OH than alpha-glucosidase. Abstract: Inhibitory effects of flavonoids on starch digestibility were well known, but the structural mechanism was not clear. This study was focused on the diverse effect of quercetin and rutin on digestibility of Tartary buckwheat starch. Results showed that quercetin and rutin reduced the starch digestion by altering starch structure in bound forms and inhibiting digestive enzyme activity in free forms simultaneously, and quercetin showed a stronger effect than rutin. Molecular docking and saturation transfer difference-nuclear magnetic resonance (STD-NMR) revealed different binding site of rutin from quercetin was due to its hydroxyl and hydrogen on the glycoside structure. Rutin interacted with enzymes mainly by CH and OH on the glycoside structure which induced steric hindrance and restricted the inhibitory effect of quercetin fraction. The glycoside structure weakened inhibition of rutin on digestive enzymes in free forms rather than influence its anti-digestive effects in bound forms with starch.